2014
DOI: 10.15623/ijret.2014.0315084
|View full text |Cite
|
Sign up to set email alerts
|

Bearing Fault Detection Using Acoustic Emission Signals Analyzed by Empirical Mode Decomposition

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…It was found that the clutch with a logarithmic profile had a better working performance in comparison with the two other profiles. Niranjan Hiremath and D.Malikarjuna Reddy 22,23 through comparative analysis, reveal that acoustic technology can detect bearing failure more effectively than vibration technology and further investigated the effect for system friction and vibration of TiN and AlCrN based PVD coatings.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the clutch with a logarithmic profile had a better working performance in comparison with the two other profiles. Niranjan Hiremath and D.Malikarjuna Reddy 22,23 through comparative analysis, reveal that acoustic technology can detect bearing failure more effectively than vibration technology and further investigated the effect for system friction and vibration of TiN and AlCrN based PVD coatings.…”
Section: Introductionmentioning
confidence: 99%